Reconstruction of Restorative Justice for Drug Users in Metro Jaya Police Jurisdiction - Paramitha Aulia Putri Nandira; Masyhar, Ali; Wulandari, Cahya (Faculty of Sharia and Law, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2026)
Drug abuse is a serious problem in Indonesia’s criminal justice system, which has traditionally been addressed through a repressive approach by treating drug users as offenders who must be punished. This approach is considered ineffective because it does not address the root cause of drug dependency. Therefore, restorative justice has emerged as an alternative approach that emphasizes recovery through rehabilitation mechanisms. This study aims to analyze the implementation of restorative justice for drug users within the jurisdiction of the Metro Jaya Regional Police and to formulate a more effective policy reconstruction based on humanitarian principles. This research employs empirical legal research with a socio-legal approach by collecting primary data through interviews with law enforcement officers and observations at the Directorate of Narcotics Investigation of the Metro Jaya Regional Police, as well as secondary data from legislation, legal literature, and institutional reports. The findings show that restorative justice has been implemented through an integrated assessment mechanism that directs drug users to medical and social rehabilitation programs. However, its implementation still faces challenges, including limited rehabilitation facilities, suboptimal inter-agency coordination, and differing paradigms among law enforcement officers. This study proposes reconstruction through strengthening rehabilitation regulations, optimizing assessment mechanisms, improving rehabilitation capacity, transforming law enforcement paradigms, and strengthening inter-agency coordination. This reconstruction is expected to enhance the implementation of restorative justice and create a more humane, recovery-oriented law enforcement system.